Hay - Muldoon, Paul 1951- (Farrar, Straus, Giroux, 1998)
An anthology of poems by an Irish-American writer. In Horses, he writes: "A sky. A field. A hedge flagrant with gorse. / I'm trying to remember, as best as I can, / if I'm a man dreaming I'm a plowhorse / or a great plowhorse dreaming I'm a man."
Keywords: Geschichte 1900-2000; English poetry -- 20th century